Protracted diarrhoea in infancy. Analysis of 82 cases with particular reference to diagnosis and management. Issue 8 (August 1977) - Larcher, V F; Shepherd, R; Francis, D E; Harries, J T
Abstract : Eighty-two cases of protracted diarrhoea in infancy presenting over a 6-year period have been analysed, with particular reference to diagnosis and management. The patients fell into 1 of 2 categories according to whether a specific diagnosis was established or not. A diagnosis (category 1) was established in 59 (72%), the commonest diagnoses being coeliac disease (33-2%), secondary disaccharide intolerance (12-2%), and cows' milk protein intolerance (12-3%). Other diagnoses included primary sucrase-isomaltase deficiency, Shwachman's syndrome, ulcerative colitis, ganglioneuroma, defective opsonization, staphylococcal pneumonia, and Hirschsprung's disease. Despite intensive investigation in diagnosis could not be established in 23 (28%) infants (category 2). Age of onset of symptoms in this group tended to be earlier than in category 1 patients, and 6 (7%) presented with diarrhoea dating from birth. Of particular interest in these 6 patients was the high incidence of associated extraintestinal anomalies, and of sibs who had died after protracted diarrhoea dating from birth. 4 of these 6 infants died, accounting for a mortality of 5% for the whole series. The remaining 17 (21%) patients in category 2 presented at a mean age of 4-9 weeks with a range of 1-18 weeks. All these 17 patients made an excellent response after institution of a chicken-based dietary formula, the details of which are presented. The pathophysiological mechanisms which may be operating in infants with protracted diarrhoea are discussed.